The Position of Minorities in Croatia and the Challenges of Multiculturalism - Testing the Applicability of Kymlicka's Minority Model - Mesić, Milan (2003)
The paper is an attempt in arguing that contemporary Croatia is a multicultural, but not (yet) multiculturalist society, since national minority rights are conceived as additive rights rather than transformative ones. The author seriously doubts that some of ethnic groups on the list of officially recognized (22) minorities can met any reasonable minority definition, and no one, except for Serbs partly, corresponds wit Kymlicka's definition.